SPATIAL IMAGINATION AND ITS ROLE IN DRAWING AND THE SCIENTIFIC PEDAGOGICAL AND PSYCHOLOGICAL BASIS OF ACHIEVING EFFECTIVENESS IN EDUCATION (Web of Teachers: Inderscience Research, 2025)
This article discusses the concept of spatial imagination, its role in drawing, as well as its scientific, pedagogical and psychological foundations for achieving effectiveness in the educational process.